Glyphosate-Induced Specific and Widespread Perturbations in the Metabolome of Soil Pseudomonas Species - Aristilde, Ludmilla; Reed, Michael L.; Wilkes, Rebecca A.; Youngster, Tracy; Kukurugya, Matthew A.; Katz, Valerie; Sasaki, Clayton R. S. (Frontiers in Environmental Science, 2017)
Previous studies have reported adverse effects of glyphosate on crop-beneficial soil bacterial species, including several soil Pseudomonas species. Of particular interest is the elucidation of the metabolic consequences of glyphosate toxicity in these species. Here we investigated the growth and metabolic responses of soil Pseudomonas species grown on succinate, a common root exudate, and glyphosate at different concentrations. We conducted our experiments with one agricultural soil isolate, P. fluorescens RA12, and three model species, P. putida KT2440, P. putida S12, and P. protegens Pf-5. Our results demonstrated both species- and strain-dependent growth responses to glyphosate. Following exposure to a range of glyphosate concentrations (up to 5 mM), the growth rate of both P. protegens Pf-5 and P. fluorescens RA12 remained unchanged whereas the two P. putida strains exhibited from 0 to 100% growth inhibition. We employed a 13C-assisted metabolomics approach using liquid chromatography-mass spectrometry to monitor disruptions in metabolic homeostasis and fluxes. Profiling of the whole-cell metabolome captured deviations in metabolite levels involved in the tricarboxylic acid cycle, ribonucleotide biosynthesis, and protein biosynthesis. Altered metabolite levels specifically in the biosynthetic pathway of aromatic amino acids (AAs), the target of toxicity for glyphosate in plants, implied the same toxicity target in the soil bacterium. Kinetic flux experiments with 13C-labeled succinate revealed that biosynthetic fluxes of the aromatic AAs were not inhibited in P. fluorescens Pf-5 in the presence of low and high glyphosate doses but these fluxes were inhibited by up to 60% in P. putida KT2440, even at sub-lethal glyphosate exposure. Notably, the greatest inhibition was found for the aromatic AA tryptophan, an important precursor to secondary metabolites. When the growth medium was supplemented with aromatic AAs, P. putida S12 exposed to a lethal dose of glyphosate completely recovered in terms of both growth rate and selected metabolite levels. Collectively, our findings led us to conclude that the glyphosate-induced specific disruption of de novo biosynthesis of aromatic AAs accompanied by widespread metabolic disruptions was responsible for dose-dependent adverse effects of glyphosate on sensitive soil Pseudomonas species.